Analysis of Leakage in Nearshore Pipelines Using Fitness for Service Method to ensure Mechanical Integrity Based on API-579 Level 3 - Elriandri, Elriandri; Priadi, Dedi (UI Scholars Hub, 2025)
The Fitness for Service (FFS) analysis is performed as a quantitative assessment to evaluate the integrity condition of a pipeline. Essentially, FFS assessment helps determine whether equipment components can operate safely despite existing deficiencies. This evaluation is carried out using the Finite Element Method (FEM). In the case of an underwater pipeline that experiences leak due to anchor pull at the flange connection, it undergoes plastic deformation and is lifted approximately 1 meter. As a mitigation step, inspection and repairs have been carried out by the company. Subsequently, modeling is performed to reconstruct the deformation process of the pipeline. Then, analyses are performed for Vortex Induced Vibration (VIV) and fatigue. The results of these analyses indicate that the pipeline is still in an acceptable condition, making it suitable for normal operation. Additionally, flow simulations are considered in the study, with various sensitivities to estimate the remaining service life of the pipeline. Based on sensitivity to flow conditions, the minimum estimated service life of the pipeline is 3 years.